Ketuntasan Belajar Siswa Melalui Penerapan Pendekatan Keterampilan Proses Pada Konsep Sistem Gerak Tumbuhan di SMA Negeri 3 Pidie - Tarmizi Tarmizi (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2011)
Implementation of process skills approach to the concept of plant motion system in SMA Negeri 3 Pidie. Research purposes to know the process of learning outcomes through the application process skills approach to the concept of plant movement. The approach used was qualitative descriptive approach types of Class Actions. This study used two cycles with four components, namely planning (planning), action (acting), observation (observing) and reflection (reflecting). Subjects in this study were students in grade XI IPA 3 year 2009/2010 amounted to 30 people. The instrument used was the test at the end of each cycle. To find out the improvement process and the thoroughness of learning were used a percentage formula. Results showed that the average grade 77.67 80% completeness level of exam success cycle I. Cycle II gained an average grade of 72.17 with 86.67% completeness level. Students generally gave positive responses (attitudes agree) on learning. It is recommended that the application of process skills approach can be used on other concepts in the biology learning as one model that can enable student learning.